(-5)+8=
9+(-3)=
(-5)+2=
(-3)-(-8)=
4-7=
(-3)-(-5)=
(-9)-(-2)=
(-6)-8=
7-(-5)=
(-7)·8=
(-6)·(-4)=
(-28):7=
63:(-7)=
(-42):(-6)=
(-3)·2·(-1)·1·(-1)·(-1)·2=
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
(-5)+8=3
9+(-3)=6
(-5)+2=-3
(-3)-(-8)=5
4-7=-3
(-3)-(-5)=2
(-9)-(-2)=-7
(-6)-8=-14
7-(-5)=12
(-7)·8=-56
(-6)·(-4)=24
(-28):7=-4
63:(-7)=-9
(-42):(-6)=7
(-3)·2·(-1)·1·(-1)·(-1)·2=12
mam nadzieję że pomogłam :D
(-5)+8=3
9+(-3)=6
(-5)+2=-3
(-3)-(-8)=5
4-7=-3
(-3)-(-5)=2
(-9)-(-2)=-7
(-6)-8=-14
7-(-5)=12
(-7)·8=-56
(-6)·(-4)=24
(-28):7=-4
63:(-7)=-9
(-42):(-6)=7
(-3)·2·(-1)·1·(-1)·(-1)·2=12